APPLYING VLADIMIR PROPP’S MORPHOLOGY OF THE FOLKTALE TO NICHOLAS SPARKS’ "THE LUCKY ONE": Received: 04th July 2023; Revised: 27th November 2023, 04th December 2023; Accepted: 06th December 2023 - Al-dihaymawee, Dr. Doaa Taher Matrood (PEOPLE: International Journal of Social Sciences, 2024)
The novel as a literary genre appeared in the eighteenth century with the rise of the mid-class as a form of entertainment. Nickola Spark is one of the modern American novelists. He is a New York Times bestseller author with over eighty million international copies in forty-five languages. The researcher aims to examine Spark’s “The Lucky One” (2008) according to the Russian folklorist and scholar Vladimir Propp’s Morphology of the Folktale (1927). Even though Propp's theory used to apply to folktales, some researchers apply it to novels, such as Nursantia (2003), entitled "The Moral Aspect in Joseph Conrad's 'Heart of Darkness'" and Salmah (2004) in his thesis entitled "The Moral Forms in Charles Dickens's 'Our Mutual Friend'". Thus, the lack of applying Propp's theory on novels in general and modern text in specific encourages the researcher to fill this gap in the study by applying Propp's Morphology of the Folktale to a modern novel, “The Lucky One” (2008). Trying to answer the following research questions: 1) Is it possible to apply Vladimir Propp’s Morphology of the Folktale (1927) to Nicholas Spark’s novel “The Lucky One”? 2) What are the good and bad morals portrayed by the main characters in “The Lucky One”? 3)How many features of Propp’s thirty-one features can be found in Nickola Spark’s “The Lucky One”?